Utilization of a Novel Low-Cost Gibto (Lupinus Albus) Seed Peel Waste for the Removal of Malachite Green Dye: Equilibrium, Kinetic, and Thermodynamic Studies - Adugna Nigatu Alene; Gietu Yirga Abate; Adere Tarekegne Habte; Desiew Mekuanint Getahun (Journal of Chemistry)
The aim of this study was to investigate the adsorption characteristics of malachite green (MG) dye onto the raw (RLAPW) and activated (ALAPW) surface of Lupinus albus seed peel waste prepared via physicochemical activation under alkaline condition as a dye adsorbent. Proximate analysis, surface area (Sears’ method), point of zero charge (pHzpc), and FTIR analysis were used to characterize the adsorbents. The effects of operational parameters such as pH (4) for ALAPW and pH (6) for RLAPW, adsorbent dose (0.2 g), initial dye concentration (30 mg/L), contact time (60 min), and temperature (298 K) were optimized. The experimental data well fitted with the Freundlich adsorption isotherm with the adsorption capacity of 7.3 mg/g for activated Lupinus albus seed peel waste (ALAPW) and Sips isotherm for raw Lupinus albus seed peel waste (RLAPW) with the adsorption capacity of 6.6 mg/g. The kinetics data well fitted to pseudo-second-order kinetic model for both adsorbents. Thermodynamic study revealed that the bioadsorption process using bioadsorbents was spontaneous and exothermic in nature. Desorption experiment was conducted and showed desorption efficiency at an acidic pH of 2. The results showed that the prepared adsorbents exhibited good adsorption capacity and can be used as an alternative adsorbent for the adsorptive removal of malachite green dyes.